Cognitive bias in rats is not influenced by oxytocin - McGuire, Molly C.; Williams, Keith L.; Welling, Lisa L. M.; Vonk, Jennifer (Frontiers in Psychology, 2015)
The effect of oxytocin on cognitive bias was investigated in rats in a modified conditioned place preference (CPP) paradigm. Fifteen male rats were trained to discriminate between two different cue combinations, one paired with palatable foods (reward training), and the other paired with unpalatable food (aversive training). Next, their reactions to two ambiguous cue combinations were evaluated and their latency to contact the goal pot recorded. Rats were injected with either oxytocin (OT) or saline with the prediction that rats administered oxytocin would display a shorter average latency to approach on ambiguous trials. There was no significant difference between latencies to approach on ambiguous trials compared to reward trials, but the rats were significantly slower on the aversive compared to the ambiguous conditions. Oxytocin did not affect approach time; however, it was unclear, after follow-up testing, whether the OT doses tested were sufficient to produce the desired effects on cognitive bias. Future research should consider this possibility.